Detection of Asymptomatic Cases of Covid-19 Pregnant Women: A Systematic Review - Prima Soultoni Akbar; Santy Irene Putri; Astri Yunita (Journal Of Nursing Practice, 2022)
Background: There have been many cases of the Covid-19 coronavirus detected in pregnant women. Data posted by the Centers for Disease Control and Prevention (CDC) shows that around 55% of pregnant women who are confirmed Covid-19 and hospitalized are asymptomatic. Purpose: The purpose of this study is to systematically review the detection of asymptomatic Covid-19 cases in pregnant women. The articles were selected from WorldCat, ProQuest, EBSCO, and PubMed Database journals published from January to April 2020. "Covid-19" or "Coronavirus" or “Coronaviruses” or "2019-nCoV" or "SARS-CoV" or "MERS-CoV" and “Asymptomatic” and “Pregnant Women” were the keywords included for this review. Articles in English or Indonesian language that were published or in press articles about Covid-19, focusing on the detection of asymptomatic Covid-19 cases of pregnant women, and the type of study is cohort were inclusion criteria. Methods: The articles using language rather than English or Indonesian were excluded. Articles for which no abstract and no provided any significant information were in the exclusion criteria. Results: A total of 628 articles achieve from the databases, the authors identified that 12 articles were analyzed. Conclusion: Based on the results of a review of several articles it can be concluded that pregnant women who do not have symptoms of Covid-19 show a large enough percentage and have a greater risk of receiving intensive care compared to women who are not pregnant.